2015
DOI: 10.1007/s11240-015-0822-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved walnut mass micropropagation through the combined use of phloroglucinol and FeEDDHA

Abstract: Despite the socioeconomic importance of walnut trees, poor rooting and recalcitrance to in vitro culture have hampered the establishment of high-yield clonal plantations. To improve walnut micropropagation, we introduced several modifications to current methods and evaluated the effects on microshoot performance and acclimatization. Nine selected genotypes (13-year-old trees) of the commercial hybrid Juglans major 209 9 J. regia were cultured in vitro on DKW-C medium supplemented with 4.4 lM BA and 50 lM IBA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…Except for cultivar 'Willamette', increasing iron concentration above MS level significantly decreased the number of shoots in all other cultivars similarly like double concentration of both iron sources in our study. Similar results were found also by LICEA-MORENO et al (2015) who focused on walnut (Juglans major) micropropagation. Increasing FeEDTA levels up to 1.5 times (10.21 mg l -1 Fe 2+ ) did not improve microshoot performance.…”
Section: Methodssupporting
confidence: 86%
“…Except for cultivar 'Willamette', increasing iron concentration above MS level significantly decreased the number of shoots in all other cultivars similarly like double concentration of both iron sources in our study. Similar results were found also by LICEA-MORENO et al (2015) who focused on walnut (Juglans major) micropropagation. Increasing FeEDTA levels up to 1.5 times (10.21 mg l -1 Fe 2+ ) did not improve microshoot performance.…”
Section: Methodssupporting
confidence: 86%
“…1d, f, g, h, i). Fe deficiency generates internerval chlorosis in young leaves in a wide variety of crops (Bergmann 1992;Broadley et al 2012); these symptoms were observed in vitro in Corylus avellana (Al Kai et al 1984), Passiflora edulis (Monteiro et al 2000), Rosa hibrida (Van Der Salm et al 1994), E. globulus microcuttings (Schwambach et al 2005), Juglans major 209 9 J. regia (Licea-Moreno et al 2015) and E. dunnii cultures (Oberschelp and Gonçalves 2016). Moreover, organogenic callus formation was observed under Fe deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Undoubtedly, only tissue culture would offer the possibility to produce high volumes of certified materials in short time periods, maintaining the genetic identity of propagated clones. Although several authors have published micropropagation protocols for various genotypes [10][11][12][13][14][15][16][17], walnuts are considered recalcitrant to tissue culture, becoming difficult the in vitro propagation of the newly realized genotypes. Additionally, the low reproducibility of micropropagation protocols is another critical factor that makes the reproduction of some varieties a more complex process; forcing to perform their adaptation on a genotype-to-genotype base, and laboratory-to-laboratory as well.…”
Section: Introductionmentioning
confidence: 99%